Pengaruh Harga, Tempat, Produk, dan Promosi pada Sikap Pelanggan terhadap Minat Pembelian saat Pemilihan Restoran Makanan - Burhanuddin Nabhan, Danu Aflah; Zakaria, Roni; Yuniaristanto, Yuniaristanto (Fakultas Teknik Universitas Tulang Bawang, 2026)
The intense competition in the food industry in Central Java requires business actors to understand the marketing factors that influence consumer behavior. The lack of understanding regarding the impact of each element of the marketing mix (4P) on consumer attitudes and purchase intentions forms the background of this study. This research aims to analyze the influence of the 4P marketing mix elements—product, price, place, and promotion—on consumer attitudes and purchase intentions toward food products in Central Java. Using a quantitative approach with the PLS-SEM method, data were collected from 500 respondents aged 15–60 through an online survey distributed via social media. The analysis results indicate that only two relationships were statistically significant. These findings suggest that in the context of the food industry in Central Java, product quality and the development of consumer attitudes are the primary factors influencing purchase intention. This study contributes to a deeper understanding of local consumer behavior and serves as a strategic reference for business actors in formulating more effective marketing strategies. Keywords: β coefficient, consumer attitude, Central Java market, marketing mix (4P), online survey.